Extra-pulmonary small cell carcinoma in the head and neck setting: The role of prophylactic cranial irradiation. Issue 6 (June 2015) - Mason, Matthew; Giuliani, Meredith; Huang, Shao Hui; Xu, Wei; Hope, Andrew; Kim, John; Bayley, Andrew; John Cho, B.C.; Goldstein, David; Jang, Raymond W; Ordonez, Bayardo Perez; Wajstaub, Sandra; et al.
Summary Head-and-neck small cell carcinoma (HN-SmCC) is a rare entity and there is limited data to support management decisions. The role of prophylactic cranial irradiation (PCI) remains controversial. A retrospective review of 21 consecutive HN-SmCCs was performed. No case received PCI. The 2-year overall survival, local, regional and distant control rates were 65%, 94%, 88%, and 76% respectively. Despite no patient receiving PCI, brain metastases were uncommon (n = 2) and routine use of PCI is not justified in this population.